First Russian Olympiad - Сергей Назарович Бубка; Мария Михайловна Булатова (National University of Physical Education and Sport of Ukraine, 2013)
First Russian Olympics, centenary of which we will celebrate in 2013, was a milestone in the history of national sport and Olympic Movement. The paper presents an analysis of situation in sport in the Russian Empire in the early 19th century as well as prehistory of First Russian Olympics that took place in Kiev; pays tribute to the initiators of this event; considers preparation for Olympics and outlines the issues related to it. The opening and closing ceremonies, and awarding of the winners are described, as well as the course of competitions in various sports included in the Olympic program are covered.